ANALISIS DAYA DUKUNG LAHAN PERTANIAN DI KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW (Agricultural Land Carrying Capacity Analysis In East Passi Sub-District, Bolaang Mongondow Regency) - Afriane Susana Ratu; Sherly G. Jocom; Tommy F. Lolowang (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
Indonesia is an agricultural country with most of its people working in agricultural sectors and should depend for much of its life on agricultural land. The decline in agricultural land is due to the increasing population. This is due to the fact that the agricultural sector has been reclaimed.The objective of this research is to analyze the agricultural land carrying capacity in Eastern Passi Sub Districts. The study went from preparation to final reporting of the study starting from October 2020 to January 2021. The data in this study is secondary data, which stems from Badan Pusat Statistik, the Eastern Passi District Office and Balai Penyuluhan Pertanian East Passi Sub District The result of this study showed that there was 3 villages has been able to grow enough food to sustain its people although have not been able to grow enough food for its population , namely the central village of Pangian, East Sinsingon, and New Insil and there was ten villages have not been able to grow enough food for its people, namely the West Pangian , Pangian, West Poopo , Poopo, South Poopo, Manembo, West Sinsingon, Sinsingon, Insil, and Mobuya.